Decolorization of Boron-Based Wood Preservatives by Ozonation for Recycling: Optimization of Process Parameters - Pantakan Yanchimpee; Usarat Thawornchaisit (My University, 2022)
Preservation of sawn timber from rubber trees with a water-soluble mixture of boric acid and borax generates a large quantity of colored wood preservative solutions and carries toxic metals, especially boron. To save costs, millers commonly reuse the colored mixtures in successive preservation cycles but regularly add boric acid and borax to maintain boron levels. However, this strategy affects both the color and the economic value of the treated wood. This paper presents a new strategy to treat the colored mixture of waterborne preservative solutions using ozonation for recycling purposes. At optimum conditions which are determined by response surface methodology, very high color removal (96 - 97 %) is achieved from ozone treatment of the wood preservatives with an initial COD concentration of 2,250 ± 40 mg/L and solution pH of 3.59 ± 0.02 for 65 min reaction time. The effluent can be reused in successive preservation cycles without degrading the wood quality in terms of the color of the processed timber and boron penetration in the end grain as well as the sides of the wood. Ozone treatment shows to be a promising color removal technology for sawn rubberwood industry, aimed at the reuse of waterborne preservatives, resulting in direct environmental and economic benefits. HIGHLIGHTS Application of ozone (O3) can be a clean technology to treat the color of aqueous solutions for in-process recycling in sawn rubberwood industry Box-Behnken design and Response Surface Methodology applied to find the optimum conditions for color removal from the mixture of boric acid and borax Recycling the mixture of boric acid and borax in a subsequent wood preservation operation gave very promising results The reusability of boron-based wood preservative solutions after ozonation minimizes the occurrence of industrial chemical waste GRAPHICAL ABSTRACT
Keywords: Borax; Boric acid; Colored; Wood Treatment and Properties